Implementation of Geoportal for Cultural Heritage Preservation of Penanggungan and Trowulan - Jaelani, Lalu Muhamad; Bachtiar, Jayed Ali (Institut Teknologi Sepuluh Nopember, 2017)
Cultural heritage is a cultural richness of the nation as a manifestation of human lifeâ€™s, thoughts and behaviors that are important for understanding the history as well as the science and culture of our ancestors. In East Java there are two cultural heritage areas have been selected by the government: Penanggungan (as of January 14, 2015) and Trowulan (as of December 30, 2013) as provincial and national cultural heritages, respectively. In this research, we built a geoportal data infrastructure for collecting, storing and visualizing the spatial distribution of cultural heritages in these two areas as one of the role in maintaining the preservation of cultural heritages. Based on our geoportal data, the location of cultural heritage located in the elevation ranged from 228 m- 1330 m (above sea level). The lowest cultural heritage was Situs Belahan and the highest one wasÂ Temple of Kama I. Trowulan Site has 75 artifact findings. This indicated that the Trowulan Site area was a residential area. While in Penanggungan site, the heritage was dominated by cultural object in the form of temple (about 32 object). It might be an indicator that Penanggungan site wasÂ a basis for ancient community worship rituals.